THU0188 EFFICACY OF FILGOTINIB IN PATIENTS WITH RHEUMATOID ARTHRITIS WITH POOR PROGNOSTIC FACTORS: POST HOC ANALYSIS OF FINCH 3. (2nd June 2020) - Aletaha, D.; Westhovens, R.; Gaujoux-Viala, C.; Adami, G.; Matsumoto, A.; Bird, P.; Messina, O.; Buch, M. H.; Bartok, B.; Yin, Z.; Guo, Y.; Hendrikx, T.; et al.
Abstract : Background: Patients (pts) with rheumatoid arthritis (RA) with poor prognostic factors (PPF) are at risk for RA progression if disease activity is not rapidly controlled. In FINCH 3 (NCT02886728 ), filgotinib (FIL)—an oral, potent, selective JAK1 inhibitor—was effective relative to methotrexate monotherapy (MTX mono) in MTX-naïve patients with ≥1 PPF—erosions, seropositivity for rheumatoid factor (RF) or anti-cyclic citrullinated peptide (CCP), or hsCRP ≥4 mg/L. 1 Objectives: This post hoc analysis examined FIL efficacy in FINCH 3 pts with multiple PPF. Methods: The global, phase 3, double-blind, active-controlled FINCH 3 study randomised MTX-naïve pts with moderately to severely active RA 2:1:1:2 to oral FIL 200 mg once daily + MTX ≤20 mg weekly, FIL 100 mg + MTX, FIL 200 mg mono, or PBO + MTX up to week (W)52. This subgroup analysis included pts with all 4 of the following PPF at baseline (PPF pts): erosions, seropositivity for RF or anti-CCP, hsCRP ≥4 mg/L, and DAS(28)CRP >5.1. Comparisons were not adjusted for multiplicity. Results: Of 1249 pts randomised and treated in FINCH 3, 510 had all 4 PPF. At baseline, relative to the overall FINCH 3 population, PPF pts had longer mean disease duration (2.4 vs 2.2 years); higher mean hsCRP (27.9 vs 17.5 mg/L), mTSS (17.9 vs 13.3), DAS28(CRP) (6.3 vs 5.7), HAQ-DI (1.76 vs 1.56), CDAI (44.3 vs 39.8), and SDAI (47.1 vs 41.5); and greater frequency of seropositivity for RF (90.6% vs 67.9%), anti-CCP (92.4% vs 68.5%), or both (82.9% vs 59.6%). Efficacy in PPF pts was comparable to data from all FINCH 3 pts (Table, Figures 1–2 ). PPF pts receiving FIL 200 mg with or without MTX vs MTX mono had higher frequencies of ACR20/50/70 response and greater improvement in HAQ-DI at W24; responses were numerically greater for FIL 200 mg + MTX vs FIL 100 mg + MTX or FIL 200 mg mono (Table ) and were evident by W12 (data not shown). Radiographic progression at W24 was lower in PPF pts receiving FIL 200 mg + MTX or FIL 200 mg mono vs MTX mono (Figure 1 ). Proportions of PPF pts receiving FIL 200 mg with or without MTX who achieved DAS28(CRP) <2.6, CDAI ≤2.8, SDAI ≤3.3, and Boolean remission at W24 (Figure 2 ) were larger vs pts receiving MTX mono and numerically greater vs pts receiving FIL 100 mg + MTX. Conclusion: FIL treatment provided rapid and deep disease control including higher rates of remission and other clinical outcomes, improved physical function, and less radiographic progression compared with MTX alone in MTX-naïve pts with RA with 4 PPF, a population at risk for severe progressive disease. In pts with 4 PPF, W24 remission rates following FIL 200 mg with or without MTX were higher vs MTX mono and numerically higher vs FIL 100 mg + MTX. References: [1]Westhovens et al. Ann Rheum Dis 2019;78(Suppl2):259–60. Disclosure of Interests: Daniel Aletaha Grant/research support from: AbbVie, Novartis, Roche, Consultant of: AbbVie, Amgen, Celgene, Lilly, Medac, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi Genzyme, Speakers bureau: AbbVie, Celgene, Lilly, Merck, Novartis, Pfizer, Sanofi Genzyme, UCB, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Cecile Gaujoux-Viala Consultant of: AbbVie; Amgen; Bristol-Myers Squibb; Celgene; Gilead Sciences, Inc.; Janssen; Lilly; Medac; Merck-Serono; Mylan; Nordic Pharma; Novartis; Pfizer; Roche; Sandoz; Sanofi; UCB, Speakers bureau: AbbVie; Amgen; Bristol-Myers Squibb; Celgene; Gilead Sciences, Inc.; Janssen; Lilly; Medac; Merck-Serono; Mylan; Nordic Pharma; Novartis; Pfizer; Roche; Sandoz; Sanofi; UCB, Giovanni Adami: None declared, Alan Matsumoto Grant/research support from: AbbVie; BMS; Eli Lilly; Galapagos; Gilead Sciences, Inc.; GSK; Janssen; Novartis; Pfizer; Sanofi; UCB; Regeneron, Consultant of: AbbVie; Gilead Sciences, Inc.; GSK; Novartis, Paul Bird Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Janssen, Novartis, Pfizer – advisor, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Janssen, Novartis, Pfizer, Osvaldo Messina Speakers bureau: Amgen; Americas Health Foundation; Pfizer, Maya H Buch Grant/research support from: Pfizer, Roche, and UCB, Consultant of: Pfizer; AbbVie; Eli Lilly; Gilead Sciences, Inc.; Merck-Serono; Sandoz; and Sanofi, Beatrix Bartok Shareholder of: Gilead Sciences Inc., Employee of: Gilead Sciences Inc., Zhaoyu Yin Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Ying Guo Shareholder of: Gilead Sciences, Inc., Employee of: Gilead Sciences, Inc., Thijs Hendrikx Shareholder of: Galapagos (share/warrant holder), Employee of: Galapagos, Gerd Rüdiger Burmester Consultant of: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Speakers bureau: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma